Biomedical Engineering Trends, Research and Technologies - Anna Komorowska, Malgorzata; Olsztynska-Janus, Sylwia (IntechOpen, 2011)
This book is addressed to scientists and professionals working in the wide area of biomedical engineering, from biochemistry and pharmacy to medicine and clinical engineering. The panorama of problems presented in this volume may be of special interest for young scientists, looking for innovative technologies and new trends in biomedical engineering.